En Bloc Cadaver Kidney Transplantation From a 9-Month-Old Donor to an Adult Recipient: Maturation of Glomerular Size and Podocyte in the Recipient. Issue 3 (March 2017) - Hirukawa, Takashi; Suzuki, Hajime; Niimura, Fumio; Fukagawa, Masafumi; Kakuta, Takatoshi
Abstract : Background: Favorable outcomes of en bloc pediatric donor kidney transplantation to adult recipients are attributed primarily to grafting of twice the nephron mass of a single kidney. Methods: The kidneys of a 9-month-old male infant were transplanted en bloc in a 56-year-old man. Biopsies were performed 1 hour postreperfusion, 6 months and 3.5 years posttransplant. Results: Warm and cold ischemia times were 21 and 426 minutes, respectively. The recipient was released from hemodialysis 10 days posttransplant and discharged 91 days posttransplant when serum creatinine was 0.9 mg/dL. At 4 years and 9 months posttransplant, serum creatinine was 1.0 mg/dL, and estimated glomerular filtration rate was 58.0 mL/min per 1.73 m 2 . The grafts increased in size until they reached adult size by 3 months posttransplant. The glomerular area and volume, respectively, increased from 5.9 × 10 3 μm 2 and 0.34 × 10 6 μm 3 at 1 hour postreperfusion to 14.9 × 10 3 μm 2 and 1.27 × 10 6 μm 3 at 3.5 years posttransplant, both of which were less than half of adult size. At 1 hour postreperfusion, podocytes were structurally immature. At 6 months posttransplant, podocyte immaturity was still evident. At 3.5 years posttransplant, podocytes were mature. Conclusions: These findings suggest that podocytes and glomerular size of pediatric donor kidneys can continue to mature in adult recipients at rates appropriate for donor age when transplanted en bloc. The maturational levels of podocytes and glomeruli may also be a factor involved in favorable outcomes of en bloc pediatric donor kidney transplantation.